A Study on Demotivating Factors in English Speaking Class (British Journal of Multidisciplinary and Advanced Studies, 2025)
In the process of learning English speaking skill, learners should have motivation and positive attitude to learn effectively. However, learners have to deal with many difficulties such as some factors that can demotivate them from participating in speaking classes. Thus, this research focused on investigating some demotivating factors in English speaking class of English-majored freshmen. Sixty English-majored freshmen at Tay Do University were chosen to participate in the study. The instruments of this research were a questionnaire and the semi-structured interview. The results showed that there were four demotivating factors in speaking class of English-majored freshmen including classroom environment, boring lectures, teacher’s behavior and lack of confidence in the students. From the findings of this research, some suggestions were given to help teachers and students in teaching and learning English speaking skill.